Effects of adapted physical activity applied on intellectual disability students toward level of emotional adjustment, self-managingand the socialization: Parent and teacher interactive research - Güvendi, Burcu; İlhan, Ekrem Levent (Journal of Human Sciences, 2017)
The purpose of the research is to investigate the effects of adapted physical activity applied on intellectual disability students toward level of emotional adjustment, self-managing and the socialization. The study was designed as pretest-posttest experimental model. Intellectual disab 12 students from 5th and 6th grade who continue their education at the public school in Esenyurt district of İstanbul in 2015-2016 academic year spring semester. Adapted physical activity program was applied the students for 2 days 1 hour per week for 12 week. Hacettepe Emotional Adjustment Scale, Self-Managing and Socialization which of subheading AAMD Adaptive Behavior Scala were used to collect data. Pretest-posttest descriptive analysis was and Wilcoxon Test was used in dependent comparisons. The results showed that decline in students’ pretest-posttest mean scores of neurotic problems and behavior problems was seen according to mothers and the school counselor of the students. An increase was observed in pretest-posttest mean scores of self-managing and socialization on behalf of the posttest. According to data from mother and school counselor, significant differences were determined between pretest-posttest on behalf of the posttest in neurotic and behavior problems which of subheading Emotional Adjustment Scale, self-managing and socialization which of subheading AAMD Adaptive Behavior Scala. Adapted physical activity applied on intellectual disability students affected positively level of emotional adjustment; self-managing and the socialization were seen. Additionally students’ socialization scores increased and emotional adjustment problems decreased were observed.